(untitled) (Journal of the College of Education for Women, 2019)
The Study was achieved adjectives physical and chemical water wells in the district ofSamarra , where a study has 42 sample groundwater in different regions of the judiciaryrandomly distributed all over the judiciary and examined in vitro.The study showed that the quality of groundwater in the general area of studyKipritateh punctuated Klordih water quality and other quality Bicarboonatih.Varied the key components of groundwater in the study area in concentrationsbetween periods of rain and drought, especially because of the cation ion exchange processesas well as mitigation as a result of filtering rain water and dominated the calcium ion,followed by sodium.As for the negative ions has dominated ion sulfate, followed by chloride on the rest ofthe ions as a result of melting rock Gypsum CaSo4.2H2O which have the ability to melt intothe water as the melting of this layer with water leads to high salinity due to increased ionconcentration sulfates as they reach the amount of dissolved salts to more than 15,000 mg / land in this case the water becomes unfit for agricultural use, but for the secondary ionsdeemed to nitrate ion secondary ions of the most important wells in the study area hasexceeded the permissible limits Iraqis and internationally.The study showed that the majority of groundwater within the study area is notsuitable for various uses Kalshrb for humans and animals, agriculture and industryclassifications used by the internationally recognized, but some of them can be used aftertreatment and for specific purposes.